Turkish Geopolitical School (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Today, Turkey holds a significant position in global politics. It is strategically located, bordered by the Black Sea and the Mediterranean Sea, which places it in a pivotal position for fostering trade, economic, cultural, humanitarian, and political relations with countries spanning three continents. In the context of contemporary world politics, Turkey has a distinctive stance and approach. These positions often play a decisive role in international affairs. Turkey frequently claims neutrality in world politics. However, questions remain as to how long this neutrality will persist and at what point Turkey will face a crucial geopolitical decision. Turkey enjoys strong relations with both Western and Eastern countries. This paper delves into Turkey’s geopolitical approaches, its role in international relations, the opportunities it faces, as well as several challenges that need further attention.